Tips Bagi Orang Tua untuk Meningkatkan Prestasi Belajar Anak - Emelia, Vivi; Prananosa, Ahmad Gawdy; Adisel, Adisel; Pektorena, Refda (JOEAI (Journal of Education and Instruction), 2022)
This study aims to determine the role of parents on students' ability to learn. This study uses a phenomenological method which aims to describe the relationship of motivation and parental guidance with student learning outcomes. The results of the study, the role of parents, especially motivation and guidance, is still very lacking so that the fluency of children in reading the Qur'an still really needs attention. This is in line with the teacher's statement that there are still some children who have not mastered the recitation of the Qur'an and are even less fluent in reading the Qur'an. Conclusion Motivation has a relationship with children's fluency in reading the Qur'an, generally children's learning achievement. The motivation and guidance of parents is very important for the fluency of children in reading the Qur'an. Keywords: Guidance, Motivation, Reading Al-Qur'an, Achievement